2023
DOI: 10.3390/agronomy13020472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liquid Manure Application Techniques on Ammonia Emission and Winter Wheat Yield

Abstract: Ammonia emissions following liquid manure application impair human health and threaten natural ecosystems. In growing arable crops, where immediate soil incorporation of the applied liquid manure is not possible, best-available application techniques are required in order to decrease ammonia losses. We determined ammonia emission, crop yield and nitrogen uptake of winter wheat in eight experimental sites across Germany. Each individual experiment consisted of an unfertilized control (N0), broadcast calcium amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…This study revealed that water inputs, such as irrigation and rainfall, were the critical factors influencing NH 3 emissions and nitrogen leaching under identical conditions. Water inputs accelerate the downward leaching of nitrogen in the biogas slurry, thereby reducing NH 3 emissions and increasing nitrogen leaching [21][22][23][24]. Rainfall volumes were observed to be 775 mm and 402 mm in the first and second years (Figure 1), respectively, indicating that rainfall was likely the predominant factor driving the aforementioned trends.…”
Section: Effect Of Biogas Slurry Substitution On N Lossmentioning
confidence: 95%
“…This study revealed that water inputs, such as irrigation and rainfall, were the critical factors influencing NH 3 emissions and nitrogen leaching under identical conditions. Water inputs accelerate the downward leaching of nitrogen in the biogas slurry, thereby reducing NH 3 emissions and increasing nitrogen leaching [21][22][23][24]. Rainfall volumes were observed to be 775 mm and 402 mm in the first and second years (Figure 1), respectively, indicating that rainfall was likely the predominant factor driving the aforementioned trends.…”
Section: Effect Of Biogas Slurry Substitution On N Lossmentioning
confidence: 95%
“…These acid traps are placed in each plot of a field experiment to collect NH 3 to assess relative differences between plots, while the wind speed corrected DTM is used on a few selected plots to scale those relative differences [12]. This approach was used in a wide range of experiments in Germany [4,[23][24][25][26][27] and Denmark [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen can be lost from the soil through processes such as leaching, denitrification, and volatilization, which lead to acidification in terrestrial systems, eutrophication of aquatic systems, and decline in biodiversity and contribute to climate change. The most commonly proposed solutions involve optimizing fertilizer doses, as well as considering the form of fertilizers used, such as slow-release fertilizers [6][7][8][9][10][11][12][13][14]. A very promising solution is the application of nitrification inhibitors [15][16][17][18][19][20].…”
mentioning
confidence: 99%